Antagonistic interaction between toxigenic strains of Aspergillus flavus and co-existing fungi of maize rhizosphere - S. ROY; A.K. ROY*, A.N. SINGH, N.L. MANDAL (Indian Phytopathology, 2008)
Aflatoxin contamination in maize is not only a post harvest problem but also has become prevalent in standing crop. To minimize pre harvest contamination in maize co-existing fungi of maize rhizosphere zone were screened having potentials either to inhibit the growth of aflatoxigenic strains of Aspergillus flavus or aflatoxin production. Out of 28 co-existing fungi isolated, on screening 11 were found to have promising inhibitory effect on growth of A. flavus as well as aflatoxin production. The antagonistic interaction of coexisting fungi against toxigenic A. flavus strain was recorded from A-E type by following Johnson & Curl’s method (1972) for the categorization of interaction behaviour. Among all antagonists, Aspergillus ochraceus, A. sydowi and Cladosporium herbarum exhibited A type (mutual intermingling); Alternaria alternata, Curvularia lunata and Monilia brunnea B type (mutual inhibition on contact); Fusarium oxysporum and F. solani C type (mutual inhibition at a distance); Aspergillus niger and Fusarium semitectum D type (inhibition on contact) and Cephalosporium roseum E type (inhibition at a distance) interaction. A. niger was found to inhibit aflatoxin production to the tune of 90% whereas, it was noticed only 30% in case of C. lunata. Mycelial dry wt. of A. flavus was also found to reduce up to 86% against A. niger.